Distraction-to-stall Versus Targeted Distraction in Magnetically Controlled Growing Rods. Issue 9 (October 2020) - Dragsted, Casper; Fruergaard, Sidsel; Jain, Mohit J.; Deveza, Lorenzo; Heydemann, John; Ohrt-Nissen, Søren; Andersen, Thomas; Gehrchen, Martin; Dahl, Benny
Abstract : Background: Consensus is lacking regarding the lengthening procedures in magnetically controlled growing rods (MCGR), and no studies have compared the outcome between different distraction principles. The purpose of the present study was to compare distraction-to-stall with targeted distraction and identify variables associated with achieved distraction. Methods: We performed a 2-center retrospective study of all children treated with MCGR from November 2013 to January 2019, having a minimum of 1-year follow-up and undergoing a minimum of 3 distractions. Exclusion criteria were single-rod constructs and conversion cases. In group 1 (21 patients), we used a distraction-to-stall (maximum force) principle where each rod was lengthened until the internal magnetic driver stopped (clunking). In group 2 (18 patients), we used a targeted distraction principle, where the desired distraction was entered the remote control before distraction. In both groups we aimed for maximal distraction and curve correction at index surgery. Achieved distraction was measured on calibrated radiographs and compared between the 2 groups using a linear mixed effects model. Univariate and multivariate analyses were performed to identify variables associated with achieved distraction within the first year. Results: Mean age at surgery was 9.5±2.0 years. Etiology of the deformity was congenital/structural (n=7), neuromuscular (n=9), syndromic (n=3), or idiopathic (n=20). Demographics and preoperative characteristics including spinal height (T1T12 and T1S1) did not differ significantly between the groups ( P ≥0.13). Time interval between distractions were mean 18 days (95% confidence interval: 10-25) shorter in group 1. Implant-related complications occurred in 10/39 patients, 5 in each group. We found no difference in achieved distraction between the groups in the linear mixed effects model. In the multivariate analysis, preoperative major curve angle was the only independent variable associated with achieved distraction. Conclusions: In 2 comparable and consecutive cohorts of patients treated with MCGR, we found no difference in achieved distraction between a distraction-to-stall and a targeted distraction principle. Preoperative major curve angle was the only independent predictor of achieved distraction. Level of Evidence: Level III—retrospective comparative study.